Brizzo Palazzo - Murphy, Richard (1999)
Casa en Brisbane adecuada al clima tropical de esta ciudad en Australia, por el arq. Donovan Hill
Keywords: CLIMA; VIVIENDAS UNIFAMILIARES; HILL, DONOVAN; AUSTRALIA; BRISBANE